Development of a Digital Career Guidance Module to Facilitate Early Career Decision-Making of Ninth-Grade Students in State Junior High Schools Across Melati District - Sri Lestari (Journal of Education and Teaching Learning, 2026)
This study aims to: (1) develop a Social Cognitive Career Theory (SCCT)-based digital career guidance module in the form of an e-flipbook to facilitate early career decision-making among ninth-grade junior high school students; (2) determine the feasibility of the developed digital career guidance module; and (3) examine the effectiveness of the digital career guidance module in facilitating students' early career decision-making.This study employed a Research and Development (R&D) approach using the ADDIE model, which consists of the stages of analysis, design, development, implementation, and evaluation. A limited trial was conducted with nine students, while a large-scale trial involved 102 students in the experimental group and 102 students in the control group from three public junior high schools in Mlati District, selected using simple random sampling. The study applied a pretest–posttest control group design, and data were collected through interviews, questionnaires (scales), and observations. The data were analyzed using qualitative and quantitative techniques to evaluate the feasibility of the module, while its effectiveness was assessed using the N-Gain test.The results indicate that: (1) a Social Cognitive Career Theory (SCCT)-based digital career guidance module in the form of an e-flipbook was successfully developed; (2) the feasibility evaluation demonstrated that the module was classified as highly feasible based on assessments by subject matter experts, media experts, and school guidance and counseling practitioners. The media expert evaluation yielded a score of 91% (highly feasible), the subject matter expert evaluation 95% (highly feasible), the guidance and counseling teacher validation 91% (highly feasible), and the student evaluation involving nine participants 77% (highly feasible); and (3) the effectiveness test showed that the digital career guidance module significantly improved students' early career decision-making. This was evidenced by an N-Gain score of 0.68 (high category) in the experimental group, compared with 0.50 (moderate category) in the control group. These findings indicate that the developed digital module is effective for use as a medium for career guidance services in junior high schools